Assessing water stress in a high-density apple orchard using trunk circumference variation, sap flow index and stem water potential - Wheeler, William D.; Black, Brent; Bugbee, Bruce (Frontiers in Plant Science, 2023)
Automated plant-based measurements of water stress have the potential to advance precision irrigation in orchard crops. Previous studies have shown correlations between sap flow, line variable differential transform (LVDT) dendrometers and fruit tree drought response. Here we report season-long automated measurement of maximum daily change in trunk diameter using band dendrometers and heated needles to measure a simplified sap flow index (SFI). Measurements were made on two apple cultivars that were stressed at 7 to 12 day intervals by withholding irrigation until the average stem water potential (ѰStem) dropped below -1.5 MPa, after which irrigation was restored and the drought cycle repeated. Dendrometer measurements of maximum daily trunk shrinkage (MDS) were highly correlated (r² = 0.85) with pressure chamber measurements of stem water potential. The SFI measurements were less correlated with stem water potential but were highly correlated with evaporative demand (r² = 0.82) as determined by the Penman-Monteith equation (ETr). This high correlation suggests that highdensity orchards resemble a continuous surface, unlike orchards with widely spaced trees. The correlations of MDS and SFI to ΨStem were higher during the early season than the late season growth. Band dendrometers are less labor intensive to install than LVDT dendrometers and are non-invasive so are well suited to commercialization.